The role of cooperation in rural development - Avdelidis, Parmenion (The Greek Review of Social Research, 1981)
The late emergence and the development of cooperatives in Greece are linked to the economic social and political evolution of the coun try. This is owing to the economic under development and the feudal nature of production relations which were still prevailing in the agrarian economy many decades after the country become indepen dent. The necessary conditions for the cooperative movement to develop only appeared when feudal relations in agriculture were abolished and land was distributed to the peasants. Though it spread in the post-war period, the cooperative move ment is behind the times both in its organization and functioning, as well as in its operations, mainly because of the anachronistic legisla tion on cooperatives, the interventions of public services, the lack of economic help and assistance from the State and the absence of capital and training. Especially with' the entry of Greece into the Common Market, cooperatives can play today an important role in helping to reorganize agriculture and adjust it to the EEC requirements, in crease the agricultural income, reduce under employment and rural depopulation. It can also take part in the cultural development of villages and the general development of the countryside.